The financial system in post-communist countries: the Polish lessons - Zbigniew Polański (Intereconomics, 1992)
The financial systems inherited by post-communist countries are damaging their economic development and make impossible macroeconomic policies aimed both at growth and economic stabilization. This incompatibility is illustrated by recent Polish experiences under both the last communist and the first non-communist government.
Keywords: 330; System Transformation